Papua’s internet ban 2020 : politics, information democracy, and digital literacy - Siagian, Muhnizar; Monika Sri Yuliarti, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Internet ban in the middle of 2019 in Papua after the outbreaks of demonstrations and riots in Papua and West Papua, still leaves various speculations and question marks. The court ruling which had won the lawsuit of the Press Freedom Defender Team against the President and the Minister of Communication and Information of Indonesia also seemed to pass by without any significant follow up. Many studies on this phenomenon in terms of law and human rights have been carried out. However, several other aspects that are also interesting and useful have not been much elaborated. This paper explores this phenomenon based on political aspects, information democracy, and digital literacy that is closely related to communication. This is a literature review that employs document study data collection techniques and interactive data analysis. From the analysis it can be found that the Papua’s internet ban relates to the effort by the Indonesian government to domesticate Papua issue in the context of politics. In terms of information democracy, there is a violation in citizen rights that intend to internationalize the issue. Finally, in the context of digital literacy, there is a need to collaborate in order to improve digital literacy skills among Papuan. The implication of this study is the richer perspective in viewing a controversial phenomenon and involves the wider community, considering that this phenomenon is very likely to still occur in Indonesia in the future.